Mutational screening of WASP gene in patients with Wiskott-Aldrich syndrome - Lan Anh, Luong Thi; Hoa, Nguyen Thanh; Hai Ha, Nguyen; Nguyen, Dang Ton (Vietnam Journal of Biotechnology, 2021)
The Wiskott-Aldrich syndrome (WAS) is a rare X-linked recessive immunodeficiency disorder characterized by thrombocytopenia and small-sized platelets, eczema, recurrent bacterial and viral infections, higher incidence of autoimmunity and an increased risk of malignancies. WAS occurs due to the mutation or loss of Wiskott-Aldrich Syndrome Protein (WASP) gene located on Xp11.22 – p11.23 of the short arm of the X chromosome. The absence of functional WASP leads to severe clinical symptoms that results in the deaths of patients if they are not diagnosed and treated early. The objective of the study was to identify mutations in the WASP gene of families with children diagnosed with WAS.The whole coding sequence and the intron-exon flanking regions of the WASP were sequenced by Sanger method. Two cases of children who has WAS were found tocarrymutations in the WASP gene. A c.702insAC mutation leadeda frameshift at position of codon 236 and terminated the protein at the position of codon 262 was identified in patient WA007 and a c.91G>A mutation that transformed glutamic acid to lysineat codon 31 was determined in patient WA010.This study provides a data set and screening of mutations in theWASP gene inVietnamese patientsto further identify the genetic causes and contribute to the clinical management and genetic counseling for the affected families.